2006
DOI: 10.1161/circulationaha.106.622340
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival in Patients Presenting With Type B Acute Aortic Dissection

Abstract: Background-Follow-up survival studies in patients with acute type B aortic dissection have been restricted to a small number of patients in single centers. We used data from a contemporary registry of acute type B aortic dissection to better understand factors associated with adverse long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
145
1
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 587 publications
(162 citation statements)
references
References 26 publications
(18 reference statements)
4
145
1
12
Order By: Relevance
“…A report from the International Registry of Acute Aortic Dissection (IRAD) identified an in‐hospital surgical mortality rate of 30% in AAD type A patients and 13% in type B 2, 3. However, long‐term outcomes for AAD patients with type B dissection are not necessarily better than those having type A. Long‐term survival of surgically treated patients with type B AAD after discharge ranges from 56% to 96% at 1 year and from 48% to 83% at 5 years 4, 5, 6, 7, 8. In contrast, for surgically treated type A patients who survive until hospital discharge, survival rates range from 52% to 96% at 1 year and from 37% to 91% at 5 years 8, 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A report from the International Registry of Acute Aortic Dissection (IRAD) identified an in‐hospital surgical mortality rate of 30% in AAD type A patients and 13% in type B 2, 3. However, long‐term outcomes for AAD patients with type B dissection are not necessarily better than those having type A. Long‐term survival of surgically treated patients with type B AAD after discharge ranges from 56% to 96% at 1 year and from 48% to 83% at 5 years 4, 5, 6, 7, 8. In contrast, for surgically treated type A patients who survive until hospital discharge, survival rates range from 52% to 96% at 1 year and from 37% to 91% at 5 years 8, 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have identified long‐term predictors of morbidity and mortality in AAD, including old age,13, 14 female sex,15 a history of atherosclerosis,4 and impaired renal function,16 all of which may be more representative of a patient's high‐risk clinical background than the severity and nature of the AAD itself. Indeed, as of yet, there may be no effective and simple marker available for evaluating severity of AAD, predicting long‐term clinical outcomes, and optimizing surgical management.…”
Section: Introductionmentioning
confidence: 99%
“…The robust self-repair of aortic dissections in mice has not been observed in humans, for whom mortality continues to increase with time after aortic dissection (21,22). in the treatment of humans, therapeutic interventions for aortic dissection include surgery or stents.…”
Section: A a B Bmentioning
confidence: 99%
“…[3][4][5][6] Late complications such as aortic enlargement and rupture may occur during follow-up in patients who receive conservative therapy at the acute phase, thereby necessitating surgery. [7][8][9] Several studies have reported that early or late complications such as aortic rupture and organ ischemia are related to whether the false lumen has been thrombosed or remains patent. 10,11) Akutsu, et al reported that a patent false lumen is strongly associated with late aortic events and mortality.…”
Section: Introductionmentioning
confidence: 99%